THE PERSPECTIVE OF LANGUAGE CULTURE IN THE DOMINATION OF THE THEME OF THE NATIONAL SONG "BAGIMU NEGERI" - Rawuh Yuda Yuwana; Sri Ananda Pertiwi (SAMPURASUN, 2022)
This research aims to find the structure of theme and rheme in the lyric text of the Indonesian national song "Bagimu Negeri (For You (my) Country)" as a data source. People in Indonesia have good meaning in the lyrics of the song "Bagimu Negeri (For You (my) Country)," which has the potential to provide a positive impetus for independent learning for language culture in the current 5.0 era. The research method used is descriptive qualitative with data collection from sentences, clauses, stanzas, and even words by documenting with listening, tapping, and note-taking techniques. The data collected are analyzed in terms of theme-rheme, with details into topical, textual, and interpersonal themes. Topical themes are divided into 2 themes, namely marked and unmarked topical themes. The results of the discussion analysis show one dominant theme in the lyrics of the Indonesian national song "Bagimu Negeri (For You (my) Country)." The results show that the lyrics of the Indonesian national anthem entitled "Bagimu Negeri (For You (my) Country)" are dominated by an unmarked topical theme, and there is no interpersonal theme found. The unmarked topical theme always has a position as the subject. There are also several stanzas of the lyrics of the Indonesian national song "Bagimu Negeri (For You (my) Country)," which have no rheme. From the perspective of language culture are; 1) bringing focus on loyalty for this country (Indonesia) by repeating a stanza "for you (my) country); 2) inviting everyone who sings this national song to give extraordinary loyalty to this country (Indonesia) by using "we" as the only subject that has rheme.